0142 Training in safe administration of intrathecal chemotherapy – is in situ simulation the answer?: A pilot study. (2nd November 2015) - Prakash, Anoop; Farooq, Omer; Durairaj, Senthilkumar; Allsup, David; Purva, Makani
Abstract : Introduction: Intrathecal injection of the wrong drug during chemotherapy treatment of cancer patients has been identified as a major patient safety issue, prompting an update of the national guidelines 1 in 2008 and an NPSA rapid response report. 2 In situ simulation helps in identification of latent errors (potential hazards in the system) 3 and effective training. We conducted an in situ simulation exercise to deliver training of safe administration of intrathecal chemotherapy. Methods: An unannounced in situ simulation activity was carried out in the Haematology intrathecal day-unit. Low fidelity simulation in the form of an actor as patient was employed. Haematology consultant, nursing staff and pharmacist were available to provide assistance to the candidate during the scenario. 4 participants from the Haematology department (2 consultants, 2 registrars) were involved. The participants completed a pre- and post-simulation questionnaire. Video debriefing was performed immediately after each scenario, focussing on adherence to guidelines, decision making, team working and leadership. Results: Three latent errors (2 equipment, 1 knowledge) were highlighted and recommendations were made to rectify these issues. Knowledge deficits were identified and addressed during the debrief. Feedback from the candidates was very positive, with unanimous appreciation of realism of the scenario. Impact on practice: Two of the latent errors were resolved promptly, leading to improved patient care. This pilot study has been well received and the results are encouraging. We believe this is the first endeavour of its kind: using In situ simulation to improve patient safety in intrathecal chemotherapy. We plan to deliver this exercise as a regular training session for the Haematology department. References: Department of Health (DH). HSC 2008/0 01 updated national guidance on the safe administration of intrathecal chemotherapy . London: DH, 2008 National Patient Safety Agency. National Patient Safety Agency, Rapid Response Report, Using Vinca Alkaloid adult minibags (adult/adolescent units) (NPSA/2008/RRR004), 2009. [Accessed on 05.05.2015] Patterson MD, et al . In situ simulation: detection of safety threats and teamwork training in a high risk emergency department. BMJ Qual Saf. 2013;22:468–477